2010
DOI: 10.5037/jomr.2010.1307
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment Protocol for Keratocystic Odontogenic Tumour: a Follow-up Study of 3 Cases

Abstract: BackgroundThe keratocystic odontogenic tumour is classified as a developmental cyst derived from the enamel organ or from the dental lamina. The treatment of keratocystic odontogenic tumour of the jaw remains controversial. The aim of this study was to report the outcome of our conservative treatment protocol for keratocystic odontogenic tumour.MethodsThree patients with different complaints referred to Oral and Maxillofacial Surgery Clinic, Faculty of Dentistry, Selçuk University. Initial biopsy was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 54 publications
2
33
0
1
Order By: Relevance
“…Other possible regions were difference of the age of the patients and size of the lesions. Hadziabdic N et al and Yildirim G et al reported that radiographically complete bone healing was achieved in about 12 months and 16 months respectively [6] [20]. Similar result was found in our case.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Other possible regions were difference of the age of the patients and size of the lesions. Hadziabdic N et al and Yildirim G et al reported that radiographically complete bone healing was achieved in about 12 months and 16 months respectively [6] [20]. Similar result was found in our case.…”
Section: Discussionsupporting
confidence: 81%
“…A general agreement was made to eradicate these lesions completely with the help of aggressive surgical approach like resection with or without continuity defects. These surgical procedures may cause severe deformity postoperatively that adversely affects the physcosocial condition of the patient particularly in young age [6]- [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The KCOT is one of the most aggressive odontogenic tumours due to its relatively high recurrence rate, its relatively fast growth, and its tendency to invade adjacent tissues including bones [8]. Based on its clinical behavior, Toller related OKC closer to the category of true benign epithelial tumours rather than a conventional cyst [9].…”
Section: Introductionmentioning
confidence: 99%